2009
DOI: 10.4093/kdj.2009.33.6.526
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low-Calorie Diets on Abdominal Visceral Fat, Muscle Mass, and Dietary Quality in Obese Type 2 Diabetic Subjects

Abstract: Background: Weight loss through low-calorie diets (LCDs) decreases visceral fat (VF). However, the effects on muscle mass, changes of dietary quality, and insulin sensitivity are unknown for Korean obese type 2 diabetic subjects. Therefore, this study examined such effects of LCDs.Methods: A total of 30 obese type 2 diabetic subjects (body mass index, 27.0 ± 2.2 kg/m2 ) were randomly assigned to an LCD or control group. Subjects on LCDs took 500~1,000 kcal fewer energy than their usual dietary intake (1,000~1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…On the other hand, several investigators have reported that SAT contributes to the development of metabolic syndrome (MS) although the correlation of SAT with MS is inconsistent and varies according to the measurement site [3]. Several studies found that the L4-L5 location is the most frequently used single-slice site to assess abdominal adiposity [19-21] whereas other studies reported that the L2-L3 site might be more appropriate [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several investigators have reported that SAT contributes to the development of metabolic syndrome (MS) although the correlation of SAT with MS is inconsistent and varies according to the measurement site [3]. Several studies found that the L4-L5 location is the most frequently used single-slice site to assess abdominal adiposity [19-21] whereas other studies reported that the L2-L3 site might be more appropriate [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies have shown that a reduction in excess abdominal fat is associated with a reduced risk of CVD [3]. Ahn et al [4] reported that diabetes mellitus (DM) patients who restrict calories have significant reductions in body weight as well as VAT, and greater improvements in insulin sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between average energy intake and total energy expenditure was -666 kcal·day -1 , average weight loss was 6.2 kg, and the energy required to lose 1 kg was 11,279 kcal. Ahn et al [ 31 ] performed a 12-week study to observe the effects of an exercise and diet program on obese adults. In that study, the average energy intake and total energy expenditure difference was -594 kcal·day -1 , average weight loss was 5.1 kg, and the energy required to lose 1 kg was 11,658 kcals.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent randomized trial, Ahn et al [ 5 ] evaluated CT data and insulin sensitivity to assess the effects of LCD and conventional DM diets on the weight, visceral fat area and thigh muscle area among Korean type 2 DM women during a 12-week interval. One group received individualized education regarding LCD every two weeks from nutritionists, while the other group received one session of conventional group education, based on the dietary guide book published by the Korean Diabetes Association.…”
mentioning
confidence: 99%